Data for: Prosocial and moral behavior under decision reveal in a public environment - Tinghög, Gustav; Andersson, Per; Erlandsson, Arvid; Vastfjall, Daniel (Linköping University, 2024)
Data from a behavioral experiment exploring the effect of public reveal on prosocial behavior and moral judgments. Here we provide raw data from a behavioral experiment exploring how altruistic behavior, cooperation and moral judgments in sacrificial dilemmas are affected by being made in public. Data was collected in a lab experiment conducted with a student sample at Linköping university. Subjects (n=374) either made decisions in a public or a private condition. We manipulate public reveal of decisions while keeping constant an environment of being observed by others. In the public condition decisions were instantly presented to other subjects on a screen next to their name and photo. We also provide data on gender age and familiar peers.

See main article for details and supplementary materials for the English translations of the question items showed to participants.

Data från en beteendeexperiment som undersökte av offentliga avslöjanden på prosocialt beteende och moraliska bedömningar. Rådata är avgiven från experimentet som undersökte hur altruistisk beteende, samarbetning, och moraliska bedömning i offerdilemman påverkas av att göras offentlig. Data samlades in i ett lab experiment som genomfördes med ett studenturval på Linköpings universitet. För mer detaljer ser engelska översättning, artikeln och supplementärt materialet inom och med datasetet.
Data för: Prosocialt och moralisk beteende under beslutnings avslöja i offentlig miljö
Keywords: experimental psychology; experimentell psykologi; charity; välgörenhet; cooperativity; samarbetsorientering; Moral Dilemmas; Moral Dilemmas; Behavioral Economics; Behavioral Economics; Experimental Economics; Experimental Economics; Psychology (Excluding Applied Psychology); Psykologi (exklusive tillämpad psykologi)